Sketching the historical development of pyrimidones as the inhibitors of the HIV integrase - Patel, Rahul V; Keum, Young-Soo; Park, Se Won (European journal of medicinal chemistry, 2015)
Heterocyclic substances perform a very unique role in drug design and discovery. This article provides the primary objectives of the analysis within pyrimidine centered new heterocyclic elements chronologically from their finding focusing on one of the essential enzyme of HIV virus particle that is integrase upon suppressing its strand transfer function. The class of compounds reviewed here includes bicyclic pyrimidines, dihydroxypyrimidines, pyrimidine-2,4-dinones, N-methylpyrimidones, pyranopyrimidine, pyridine-quinoline conjugates, pyrimidine-2-carboxamides, N-3 hydroxylated pyrimidine-2,4-diones as well as their various substituted analogues. Such initiatives released an effective drug Raltegravir as a first FDA approved anti-HIV integrase inhibitor as well as several of its derivatives along with other pyrimidones is under clinical or preclinical growth. Some of the provided scaffolds indicated dual anti-HIV efficacies against HIV reverse transcriptase and integrase enzymes at both cites as 3'-processing and strand transfer, while several scaffolds exhibited potency against Raltegravir resistant HIV mutant strains determining themselves a potent class of compounds having appealing upcoming implementations. Connections of the new compounds' molecular structure and HIV viral target has been overviewed to be able to accomplish further growth of promising anti-HIV agents in future drug discovery process.
Keywords: objevování léků; Humans; HIV-integrasa; lidé; Pyrimidinones; HIV Integrase Inhibitors; Drug Discovery; inhibitory HIV-integrasy; HIV Integrase; pyrimidinony